Metabolic Adaptations of Uropathogenic E. coli in the Urinary Tract - Mann, Riti; Mediati, Daniel G.; Duggin, Iain G.; Harry, Elizabeth J.; Bottomley, Amy L. (Frontiers in Cellular and Infection Microbiology, 2017)
Escherichia coli ordinarily resides in the lower gastrointestinal tract in humans, but some strains, known as Uropathogenic E. coli (UPEC), are also adapted to the relatively harsh environment of the urinary tract. Infections of the urine, bladder and kidneys by UPEC may lead to potentially fatal bloodstream infections. To survive this range of conditions, UPEC strains must have broad and flexible metabolic capabilities and efficiently utilize scarce essential nutrients. Whole-organism (or “omics”) methods have recently provided significant advances in our understanding of the importance of metabolic adaptation in the success of UPECs. Here we describe the nutritional and metabolic requirements for UPEC infection in these environments, and focus on particular metabolic responses and adaptations of UPEC that appear to be essential for survival in the urinary tract.